REORIENTASI PERAN BIROKRASI DALAM MENINGKATKAN PROFESIONALITAS PELAYANAN PUBLIK - F. Winami F. Winami (Jurnal Cakrawala Pendidikan, 1999)
Social reality shows that the i~npressiona bout the performanceof the bureaucracy is that it is rigid. centralized. untouchedby change, and inefficient. However. the presentera ofeconomic and informational globalization and the rapiddevelopment of science, technology, and art demand thatthere are also changes in the administration system thatsuppol-ts the bureaucracy. Therefore, there needs to be areorientation of the bureaucracy to make it more creative.The changes in need of attention are, among others. 1.the changes of the form and structure of the bureaucracy which are stable-mechanical into those which are organicadaptable,2. the changes of the principles producing classicmanagement into those producing new public management,and 3. the changes in the form of decentralization/redistribution of power to the people to encourage theirheightened pasticipation in all aspects of development.The university as an agent of reformation and producerof quality bureaucrats also has to change to be synchronouswith the attempted changes above. Therefore, changesin the curriculum need to be made to make it more adaptableand a university managerial system that stimulates creativeattitude needs to be adopted and developed.